PERAN GURU DALAM MEMBERIKAN PEMAHAMAN TERHADAP PESERTA DIDIK DISLEKSIA PADA PROSES PEMBELAJARAN DI MIN DONGGALA - Nur Afifah Sakka, Nur Afifah Sakka; Arifuddin M Arif, Ufiyah Ramlah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study investigates the role of teachers in helping students with dyslexia understand learning materials at MIN Donggala. Using a qualitative descriptive method, data were collected through interviews, observations, and documentation. The research found that teachers assume four primary roles: class manager, facilitator, demonstrator, and evaluator. As class managers, teachers address the challenge of students’ lack of focus by applying active and differentiated learning approaches. As facilitators, they overcome time limitations through private guidance and provide motivational support to build students' self-confidence. As demonstrators, teachers use audiovisual media to improve comprehension. As evaluators, they accommodate slower processing speeds by giving extra time and simplifying language in assessments. These roles highlight teachers’ adaptive strategies in promoting inclusive education and ensuring that students with dyslexia receive appropriate support throughout the learning process.